Efektifitas Pemberian e-Booklet Tentang Permasalahan Menyusui Terhadap Peningkatan Pengetahuan Dokter Umum di Puskesmas Kota Malang - Ahmad Syauqie Almuhdar; Dewi Martha Indria; Faridah Rusnianah (Jurnal Kesehatan Islam : Islamic Health Journal, 2018)
ABSTRACTBackground : Breastfeeding problems are caused by breast problems which are one of the factors that loss of the interest mothers to breastfeed. A third of women aged 25 years do not breastfeed because of breast swelling. In addition, inverted nipple, flat nipple, clogged duct, mastitis, and breast abscess are also cause mother’s reluctance to breastfeed. General practitioner at Public Health Center as primary care physicians should have a good knowledge how to troubleshoot breastfeeding problems. A good knowledge will help general practitioner to resolve the cases of confession. One way to increase to knowledge by using learning media. Today almost everyone has a smartphone. It is encouraged to use electronic based learning media in the form of e-booklet. This research aims to determine The Effectiveness of E-booklet on Breastfeeding Problems to Increase the Knowledge of General Practitioner at Public Health Center Malang City. Methods : This type of research is the quantitative, using the quasi experiment method with the research design One Group Pretest-Posttest Design with total sampling. The population is known for 35 that is all the general practitioners working at Public Health Center with inclusion creteria, like general practitioners who are willing to be respondents and functional physicians who work in public health center of Malang city. Sample obtained as many as 23 people. Questionnaires were given to measure knowledge before and after the giving of e-booklet. Datas were analyzed by paired sample t test (p < 0,05). Results : There is an average difference between the value before and after the e-booklets. Average posttest value is higher than pretest. Conclusion : E-booklet is effectively improve general practitioner’s knowledge of breastfeeding problems.Keywords : Knowledge, General Practitioner, E-booklet, Breastfeeding Problems, Public Health Center